PELATIHAN MANAJEMEN DALAM MENCIPTAKAN LINGKUNGAN KERJA YANG KONDUSIF DAN RELIGIUS DI KANTOR CAMAT RAMBUTAN, BANYUASIN - Yuniar, Yuniar; Afriantoni, Afriantoni; Aldyandra, Aldyandra; Fitrianti, Eka; Firzal, Juanda; Muhlisin, M. Oky; Marlina, Marlina (MAJU : Indonesian Journal of Community Empowerment, 2024)
This community service aims to improve the quality of the work environment at the Office of the Sub-District Head of Rambutan, Banyuasin through management training emphasizing the creation of a conducive and religious work atmosphere. The training is designed to span three days, covering planning, implementation, and evaluation. On the first day, the focus is on planning and preparation, including coordination with relevant parties, determining training materials and speakers, and logistical arrangements. The second day constitutes the core of the training, where participants receive instruction on productivity, religious values, and strategies for optimizing productivity in a conducive and religious work environment. This session also includes group discussions and practical exercises to apply the learned concepts. The third day involves training evaluation and policy formulation to ensure the sustainability of training outcomes. The expected outcomes of this training include improved mental well-being and work motivation among employees, reduced stress levels, and the establishment of a more harmonious and blessed work culture. Leaders with high ethics and empathy are expected to foster a positive organizational culture, enhance interpersonal relationships among employees, and advance the quality of public services. Expected outputs from this initiative include comprehensive documentation of training materials, an evaluative report, participant certificates, and a clear follow-up plan. This documentation will serve as a reference for future training sessions and educational resources. Through this training, it is anticipated that employees at the Office of the Sub-District Head of Rambutan will better appreciate religious values in their daily work, enhance teamwork among colleagues, and contribute to improved public services oriented toward community welfare